Evaluating the effects of community-based programs on viral rebound and viral suppression among HIV-positive orphaned and vulnerable children receiving antiretroviral treatment: Findings from the ACHIEVE project in Tanzania - Amon Exavery; Daisy Kisyombe; Alison Koler; John Charles; Nemes Mallya; Erica Kuhlik; Asheri Barankena; Rose Fovo; Godfrey Martin Mubyazi; Tom Ventimiglia; Jennifer Mulik; Gloria Sangiwa; et al. (PLoS ONE, 2026)
Background Achieving and sustaining viral load suppression (VLS) among children living with HIV remains challenging despite the availability of antiretroviral therapy (ART), primarily due to adherence difficulties. This study evaluated the effects of three interventions under the ACHIEVE project on viral load outcomes (viral rebound and viral suppression) among HIV-positive orphaned and vulnerable children aged 0–17 years (hereafter referred to as CLHIV) receiving ART in Tanzania. Methods This is a longitudinal analysis of 26,257 CLHIV who are beneficiaries of the ACHIEVE project in Tanzania, each with at least two viral load (VL) test results between 2021 and 2023. VL outcomes were assessed using two analytic groups: Group 1 included 21,448 CLHIV with undetectable VL (<50 copies/mL) at baseline, where those maintaining undetectable VL were compared with those experiencing viral rebound (VL ≥ 50 copies/mL) at follow-up. Group 2 comprised 4,809 CLHIV with detectable VL (≥50 copies/mL) at baseline, where those achieving undetectable VL at follow-up were compared with those who did not. The study used a multivariable logistic regression model and propensity score matching (PSM) to evaluate the effects of ACHIEVE project interventions–WORTH Yetu economic strengthening, linkage to teen/paediatric clubs, and health insurance–on viral rebound (Group 1), and the achievement of an undetectable viral load (Group 2). Findings Overall, 13.1% (2,805/21,448) of Group 1 CLHIV experienced viral rebound at follow-up. CLHIV who received ACHIEVE interventions were 23.2% less likely to experience viral rebound compared to those who did not (aOR = 0.768, 95% CI 0.668–0.882, p < 0.001). In Group 2, 70.9% (3,411/4,809) achieved an undetectable viral load at follow-up, with those who received ACHIEVE interventions being 31.9% more likely to achieve an undetectable viral load compared to those who did not (aOR = 1.319, 95% CI 1.059–1.643, p = 0.014). These findings were confirmed in the PSM analysis (viral rebound: β = – 0.047, 95% CI –0.072 – –0.021, p < 0.001; achieving undetectable viral load: β = 0.10, 95% CI 0.04–0.16, p = 0.001). Conclusion The ACHIEVE project interventions were significantly associated with a reduced likelihood of viral rebound, and an increased likelihood of achieving undetectable viral load among CLHIV, highlighting their potential to enhance ART outcomes. These findings suggest that expanding similar community-based interventions could further contribute to HIV treatment efficacy and support more children in achieving and maintaining an undetectable viral load, particularly those at risk of viral rebound or persistent high viral load. Future research should explore strategies for scaling these interventions and evaluating their long-term impact.